2022
DOI: 10.3390/diagnostics12081799
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Liquid Biopsies in Non-Small-Cell Lung Cancer

Abstract: The concept of liquid biopsy as an analysis tool for non-solid tissue carried out for the purpose of providing information about solid tumors was introduced approximately 20 years ago. Additional to the detection of circulating tumor cells (CTCs), the liquid biopsy approach quickly included the analysis of circulating tumor DNA (ctDNA) and other tumor-derived markers such as circulating cell-free RNA or extracellular vesicles. Liquid biopsy is a non-invasive technique for detecting multiple cancer-associated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 159 publications
(158 reference statements)
1
10
0
Order By: Relevance
“…Recently, some studies demonstrated that the positive ctDNA was associated with the poor survival in pancreatic cancer [49], breast cancer [50], lung cancer and biliary tract cancer [51,52]. Both our meta-analysis and Swathikan Chidambaram et al's meta-analysis [17] demonstrated the association between the ctDNA and the prognosis of EC patients.…”
Section: Discussionsupporting
confidence: 62%
“…Recently, some studies demonstrated that the positive ctDNA was associated with the poor survival in pancreatic cancer [49], breast cancer [50], lung cancer and biliary tract cancer [51,52]. Both our meta-analysis and Swathikan Chidambaram et al's meta-analysis [17] demonstrated the association between the ctDNA and the prognosis of EC patients.…”
Section: Discussionsupporting
confidence: 62%
“…NGS is widely used for the detection of ctDNA: it allows simultaneous sequencing of different genomic regions in many samples, it is also able to quantitate gene copy number variations, including gene amplification, and to identify chromosomal rearrangements such as oncogenic fusions. Besides, NGS is able to calculate the frequency of the variant allele ( Rolfo et al, 2018 ; Fernandes et al, 2021 ; Pesta et al, 2022 ). NGS also allows the comprehension of tumour genetic features and provides crucial information on tumour microenvironment and immune response, that might drive the response to immuno-therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, liquid biopsy (LB), consisting of the analysis of tumour-released nucleic acids circulating in body fluids, such as blood, could provide a non-invasive and well-tolerated approach for tumour investigation. It allows the detection of circulating tumour DNA (ctDNA) carrying molecular tumour markers, which are more representative of the entire tumour and enable to follow disease evolution and dynamic changes in the molecular profile ( Pérez-Callejo et al, 2016 ; Rijavec E et al, 2020 ; Bonanno et al, 2022 ; Pesta et al, 2022 ). In addition, in advanced/metastatic NSCLC, liquid biopsy has the potential to drive target therapy, by monitoring the response to treatment and identifying the possible molecular mechanisms of therapy resistance.…”
Section: Introductionmentioning
confidence: 99%
“…ctDNA can also be analyzed by covering the total genome using WGS. 249 Robust qPCR and sequencing strategies have facilitated ctDNA-based detection of variants and phenotypic characterization of key driver genes like KRAS, BRAF, ALK, and identify key mutations like L858R and T790M (linked to resistance) to predict targeted therapeutic options for non-smallcell lung cancer patients (NSCLC). 250,251 KRAS mutations occur in >90% of pancreatic cancer and increasing levels of these mutations during and post-treatment are associated with worse PFS and OS.…”
Section: Proteomicsmentioning
confidence: 99%